2021
DOI: 10.3389/fnetp.2021.755016
|View full text |Cite
|
Sign up to set email alerts
|

Time in Brain: How Biological Rhythms Impact on EEG Signals and on EEG-Derived Brain Networks

Abstract: Electroencephalography (EEG) is a widely employed tool for exploring brain dynamics and is used extensively in various domains, ranging from clinical diagnosis via neuroscience, cognitive science, cognitive psychology, psychophysiology, neuromarketing, neurolinguistics, and pharmacology to research on brain computer interfaces. EEG is the only technique that enables the continuous recording of brain dynamics over periods of time that range from a few seconds to hours and days and beyond. When taking long-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 138 publications
0
21
0
Order By: Relevance
“…Thirdly, we omitted the investigation of the effect of sex due to the unbalanced representation of females and males across the age groups and the whole sample. Finally, information about the time of the day in which acquisitions took place was not available and circadian and ultradian rhythms can impact spectral characteristics of EEG signals (Lehnertz et al, 2021). These limitations might be addressed by the addition of further information and extensions to the LEMON dataset or combining it with other openly available datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, we omitted the investigation of the effect of sex due to the unbalanced representation of females and males across the age groups and the whole sample. Finally, information about the time of the day in which acquisitions took place was not available and circadian and ultradian rhythms can impact spectral characteristics of EEG signals (Lehnertz et al, 2021). These limitations might be addressed by the addition of further information and extensions to the LEMON dataset or combining it with other openly available datasets.…”
Section: Discussionmentioning
confidence: 99%
“…With many of the aforementioned techniques to derive characteristics of pairwise interactions from observations, interactions are assumed to be constant (at least during the investigated time interval). This assumption might not be fully justified for the inherently nonstationary system brain, notwithstanding the wide range of endogenous and exogenous biological rhythms impacting differently on its structure and function (Lehnertz et al, 2021). Another and long-standing issue (e.g., Zentgraf, 1975) centers around identifying and characterizing higher-order interactions, i.e., interactions that cannot be reduced to pairwise interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Early network‐based seizure‐prediction studies 48–51 have reported limited predictive performance from temporal changes of global network characteristics that assess the network's functional segregation, integration, or robustness. This can be ascribed to various biological rhythms that distinctly affect brain networks 52 . In contrast, a well‐above‐chance‐level 37 predictive performance was reported recently for temporal changes of characteristics of single network constituents, 53–55 based on which network mechanism for the epileptic brain's transition into the pre‐ictal state was proposed.…”
Section: Brain Network In Seizure Forecastingmentioning
confidence: 93%
“…This can be ascribed to various biological rhythms that distinctly affect brain networks. 52 In contrast, a wellabove-chance-level 37 predictive performance was reported recently for temporal changes of characteristics of single network constituents, [53][54][55] based on which network mechanism for the epileptic brain's transition into the pre-ictal state was proposed. The transition is characterized by a rearrangement of the larger epileptic network's path structure, which results in a formation of bottlenecks that impairs physiologic brain communication-an important factor in brain disorders.…”
Section: Seizure Forecastingmentioning
confidence: 97%